ROS1 positive non-small cell lung cancer with pulmonary embolism in a 22-year woman - Ananda Datta (Monaldi Archives for Chest Disease, 2020)
ROS1-rearrangement occurs in 1-2% of non-small cell lung cancer (NSCLC). This mutation is predominantly seen in relatively young, non-smoker, female with adenocarcinoma. Association of pulmonary embolism with ROS1-rearranged NSCLC has been suggested. We report a case of a 22-year-old woman with ROS1-positive NSCLC and pulmonary embolism. This case possibly represents the youngest patient in the literature.